Diagnosis Cepat Aspergilosis Paru Kronik pada Pasien Penyakit Resparasi: Harapan bagi Daerah Bersumber Daya Terbatas - Rozaliyani, Anna (Majalah Kedokteran Indonesia, 2023)
Introduction: Chronic pulmonary aspergillosis (CPA) is a global health burden, however the diagnosis is still challenging due to non-specific clinical and radiological features. To overcome this problem, the lateral flow assay to detect Aspergillus-specific antibodies has the potential for rapid CPA diagnosis (point-of-care test/POCT). The aim of this study is to describe the profile of POCT Aspergillus-specific antibody detection in various populations as part of CPA diagnosis in Indonesia.Methods: This study is a part of previous CPA studies conducted in Jakarta between 2018-2021. The tests were carried out at the Laboratory of Parasitology Department, Faculty of Medicine Universitas Indonesia. All sera were tested using Aspergillus-specific immunochromatography lateral flow assay (LDBio, Diagnostics, Lyon, France) according to the manufacturer's instructions.Results: There were 314 patients' sera derived from four groups: post-TB (n=82), active TB (n=105), uncontrolled-asthma (n=50), and lung cancer (n=77). The positive results of LDBio Aspergillus ICT were 43% in post TB, 11% in active TB, 16% in uncontrolled asthma, and 14% in lung cancer patients. Further analysis revealed that the prevalence of CPA was 6-22% in those populations.Conclusion: The LDBio Aspergillus ICT has the potential as a POCT for early diagnosis of CPA. The risk of CPA was found highest in the post-TB group compared to others.